The Alon-Tarsi number of cupolarotundas and gyroelongated rotunda - Li, Zhiguo; Gai, Yujia; Shao, Zeling (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
The Alon-Tarsi number of a graph G is the smallest k so that there exists an orientation D of G with max outdegree k - 1 satisfying the number of even Eulerian subgraphs different from the number of odd Eulerian subgraphs. This paper is devoted to the study of the Alon-Tarsi number of cupolarotundas and gyroelongated rotunda.